A Study Examining the Current Status of Microfinance in India - Mr. Sunny Masand; Mr. Maulik Chandnani; Mr. Shailendra Singh Barath (Journal of Advanced Zoology, 2022)
In a country like India, where 70 percent of the population resides in rural areas and 60 percent are dependent on agriculture, according to World Bank reports, microfinance emerges as a crucial instrument for providing financial services to the poor and low-income individuals. Microfinance encompasses various financial services tailored to the needs of economically disadvantaged segments of society, including loans, savings, credit, insurance, money transfer, and other basic financial services. Its delivery mechanisms are designed to ensure that these products reach remote and impoverished areas effectively. Microfinance is widely recognized as an effective tool for poverty alleviation in India, offering credit and financial services to economically disadvantaged individuals in both urban and rural settings. Microfinance institutions in India comprise a diverse range of organizations, including NGOs, credit unions, NBFCs, cooperatives, and banks. The future of microfinance in India is largely dependent on self-help groups (SHGs), which play a significant role in facilitating access to financial services for underserved communities. The primary focus of this paper is to examine the performance and role of microfinance institutions in the overall development of India, particularly in addressing the financial needs of marginalized populations. Keywords: microfinance, MFI’s, growth of microfinance, poverty, SHGs